The form of the equation of the circle is
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
(h, k) is the center
r is the radius
Let us compare it with the given equation to find the center and the radius
![(x+1)^2+(y-1)^2=36](https://img.qammunity.org/2023/formulas/mathematics/college/d9g1i805dyk6hf3fbo1apeieo33qqm6v2s.png)
From the comparing
h = -1
k = 1
r^2 = 36
Find the square root of 36 to get r
![\begin{gathered} r=\sqrt[]{36} \\ r=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yocokbcnxpqyu7dxkqc3h2lrmknie1agz2.png)
The center is (-1, 1) and the radius is 6